Notas sobre José Carlos Mariátegui y los „estudios culturales‟ - Fereyra, Silvana (Diálogos Latinoamericanos, 2011)
In this article our purpose is to establish a dialogue between Mariátegui and „cultural studies‟, taking into account variants of the field in Europe, US and Latin America. In the first place, we analyze some topics of Mariategui‟s work, like race, tradition and literature in Perú, that may be considered nodal themes in 'cultural studies' tradition. Secondly, we explore his approach to cultural issues starting from an overall view of his career (trade-union, political and intellectual) and in connection with his interpretation of Marxism. Our hypothesis is that the analysis of Mariategui‟s reflections will give us new conceptual and methodological tools to consider a number of issues that are currently present on the agenda of 'Latin American cultural studies', but it will also allow us to introduce new arguments in the debate on institutionalization and de-politicization of the field.